Aerospace series. Cables, electrical, for general purpose, single and multicore assembly. XLETFE Family. BJ. Nickel plated copper. Operating temperatures, between -65°C and 150°C. Single extruded wall for use as cable cores or within equipment in areas of high vibration, cable flexing and fluid contamination. UV laser printable. Product standard Part 009, (29th February 2012) - British Standards Institution,
No abstract available